Contribution to the knowledge of the spring butterfly fauna of the Republic of Macedonia (Lepidoptera: Papilionoidea & Hesperioidea) - Rudi Verovnik (Natura Sloveniae)
In spring 2010, we encountered 60 butterfly species during field surveys centred mainly in the under-surveyed southeastern part of the Republic of Macedonia. We visited 23 localities, where several interesting observations were made. Among these, new sites of some rare species such as Pontia chloridice, Pieris krueperi, Plebejus sephirus, Scolitantides orion, Tarucus balkanicus, Melitaea ornata, Carcharodus orientalis, and Erynnis marloyi should be mentioned. Such a high number of species observed indicates an overall high butterfly diversity of this region, particularly in the lower Vardar valley. Here, several specific habitats hosting rare and threatened species were discovered. The anthropogenic pressure on important butterfly habitat is still low in the surveyed area; however, the first signs of large scale abandonment are already visible.